Komitmen perangkat desa dalam upaya percepatan penurunan stunting: Studi kualitatif di Kecamatan Pakis, Kabupaten Magelang - Syuja' Rafiqi Arifin; Yhona Paratmanitya; Pramitha Sari; Aripin Ahmad; Ferissa Safira (Poltekkes Kemenkes Aceh, 2024)
Background: In 2021, the Indonesian government aims to reduce the stunting rate to 14% by 2024. Efforts to accelerate stunting reduction have five strategic pillars, including commitment and leadership vision. The national strategy for accelerating stunting reduction is through strengthening commitment and strengthening the vision of leadership, as stated in Presidential Regulation No. 72 of 2021.Objectives: To identify the commitment of village officials in Pakis District through perceptions, efforts, and the role of village officials in accelerating stunting reduction so far in Pakis District, Magelang Regency.Method: The research method used a phenomenological qualitative approach with data collection using in-depth structured interview techniques. The main informants in this study were the village head, village secretary, and village treasurer, and the supporting informants were the hamlet heads. The research was conducted during the community service program and KKN-T Gotong Royong Prevent Stunting (Gong Ceting), which was conducted from October to December 2022. The research location was in 3 villages in Pakis Sub-district, namely: Kenalan Village, Gumelem Village, and Jambewangi Village. The limitation of this research is to identify commitment in efforts to accelerate stunting reduction.Results: The results of the study illustrate that there is a commitment of Pakis District village officials to accelerating the reduction of stunting. This study illustrates that village officials have played a role and made efforts to accelerate stunting reduction in the village. In realizing and growing organizational commitment, there are three aspects that are considered, namely: perception, role, and effort.Conclusion: This study illustrates that village officials in Pakis Sub-district are committed to accelerating stunting reduction.